IMPLEMENTASI DAN PELATIHAN APLIKASI POS DI SALON SINTA - nabila, ariyani (ABDIMAS : Jurnal Pengabdian Masyarakat, 2025)
Implementation of information technology through Point of Sale (POS) applications is an effective solution for improving operational efficiency and service quality for small and medium businesses. This research focuses on the implementation and training in using the POS application at Salon Sinta, a beauty salon business that still uses a manual recording system. Manual systems often cause long queues, recording errors and service delays, especially when the salon is busy. The POS application designed not only records transactions, but is also able to manage customer, product, stock and financial data in an integrated manner. The methods used in this research include direct observation of salon operational activities, interviews with owners and employees to understand business needs, application development that suits the salon's needs, as well as implementation and training of employees in using the POS system. The training process is designed to ensure all employees can operate the application easily and efficiently. Implementation results show significant improvements in transaction processing speed, recording accuracy, and overall data management. This application also helps reduce employee workload so they can focus more on customer service. This research makes a real contribution in encouraging digital transformation in